Seismic response of buried pipes in sloping medium dense sand. Issue 170 (July 2023) - Fan, Jiying; Zhao, Xin; Liu, Jingwen; Huang, Bo
Abstract: Dynamic centrifugal experiments are conducted to explore the seismic response of buried pipes in sloping medium dense sand. Different ground inclination angles θ, different amplitudes of seismic wave, different boundary conditions of pipe, and different burial depths H are investigated. Test results show that the excess pore pressure (EPP) is asymmetrically distributed around the pipe, with the value along the springline on the uphill side notably larger than that on the downhill side. The generation of EPP continues after the shaking. EPP around the free-moving pipe is smaller and dissipates faster than that around the stationary pipe. Compared with the horizontal ground, 10° and 20° ground inclinations result in a 1.3–1.9 folds increase in EPP beneath pipe and a 2.4–3.4 folds increase in peak uplift displacement. Lateral movement of pipe towards the downhill side and rotation of pipe towards the uphill side are linearly correlated and both increased with a shallower H and larger θ . Due to the pipe-soil interaction, soil displaces along a series of quasi-circular slip surfaces extending from the ground surface on the uphill side to the ground surface on the downhill side. Thus, enough burial depth is required to mitigate the greater displacement of pipe and soil arising from the ground inclination. Highlights: Investigate the effect of ground sloping on the seismic performance of buried pipe. Explore the difference in excess pore pressure around the free-moving pipe and the stationary pipe. Study soil displacement and propose a quasi-circular slip model for the sloping ground.